Faktor-faktor yang Mempengaruhi Kejadian Hamil di Luar Nikah Pada Remaja Putri dalam Masa Pandemi Covid-19 di Wilayah Kerja Puskemas Tujuh Ulu Palembang 2021 - Parti Senja; Suprida Suprida; Sri Handayani (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Teenage pregnancy has a negative impact on both mother and baby. According to WHO, girls aged 10-14 years have a five times greater risk of dying in pregnancy and childbirth than women aged 20-24 years. Child marriage causes early pregnancy and childbirth which is associated with a high mortality rate and mothers who give birth under the age of 18 also have a risk of death in infants, namely premature and stunted babies, pregnant at a young age are also prone to bleeding, miscarriage. , pregnant with grapes and pregnant prematurely during pregnancy even give wrong parenting to children because of the limited knowledge of the nature of motherhood in psychology. This study aims to determine the relationship between knowledge, attitudes and the role of parents simultaneously with the incidence of pregnancy out of wedlock in adolescent girls during the Covid-19 pandemic in the Seven Ulu Public Health Center working area, Palembang in 2021. This study used an analytical survey with quantitative methods with a design design. cross sectional research, where the dependent variable is pregnant out of wedlock and the independent variable is knowledge, attitudes and the role of parents are collected simultaneously. The population in this study were all pregnant women in the Work Area of the Tujuh Ulu Health Center, Palembang in 2021, which were estimated to be 124 pregnant women from January-June. The sample is some of the mothers who are in the Working Area of the Tujuh Ulu Public Health Center Palembang in 2021. From the results of research that has been carried out at the Tujuh Ulu Health Center Palembang, it can be concluded that there is a partial relationship between knowledge and the incidence of pregnancy outside of marriage at the Tujuh Ulu Public Health Center Palembang in 2021, there is no partial relationship between maternal attitudes and the incidence of pregnancy outside marriage at the Tujuh Ulu Public Health Center Palembang in 2021 and there is a partial relationship between parental roles and the incidence of pregnancy outside of marriage at the Puskesmas.